1977
DOI: 10.1111/1523-1747.ep12496022
|View full text |Cite
|
Sign up to set email alerts
|

Oral Methoxsalen Photochemotherapy for The Treatment of Psoriasis: a Cooperative Clinical Trial

Abstract: Extensive psoriasis in 1,308 patients has been treated two or three times a week with oral 8-methoxypsoralen followed by high intensity, long-wave ultraviolet light (PUVA). Excluding 169 patients still under early treatment, psoriasis cleared in 88% and failed to clear in 3%. One percent dropped out due to complications of treatment, and 8% for other reasons. The twice-a-week schedule was superior for patients with lighter skin types. Once a remission was induced, there was no difference in its maintenance whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
1
3

Year Published

1979
1979
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 476 publications
(113 citation statements)
references
References 4 publications
6
101
1
3
Order By: Relevance
“…The results in 21 adult caucasian patients with widespread plaque psoriasis was most impressive -all the patients cleared completely. Subsequent reports on greater numbers of patients have claimed similar impressive results , Melski et al 1977. Psoriasis cleared in 88% of 1308 patients with extensive psoriasis treated in the American Cooperative Clinical Trial, and failed to clear in only 3%.…”
Section: Institute Of Dermatology St John's Hospitalfor Diseases Of Tmentioning
confidence: 79%
See 1 more Smart Citation
“…The results in 21 adult caucasian patients with widespread plaque psoriasis was most impressive -all the patients cleared completely. Subsequent reports on greater numbers of patients have claimed similar impressive results , Melski et al 1977. Psoriasis cleared in 88% of 1308 patients with extensive psoriasis treated in the American Cooperative Clinical Trial, and failed to clear in only 3%.…”
Section: Institute Of Dermatology St John's Hospitalfor Diseases Of Tmentioning
confidence: 79%
“…Other applications of photochemotherapy Some workers have found photochemotherapy effective in erythrodermic psoriasis (Melski et al 1977) although dosimetry is difficult and improvement slow. Complete clearing of skin lesions and relief of systemic symptoms was achieved in eight patients with generalized pustular psoriasis .…”
Section: Potential Side Effects Mutaqenicity and Neoplastic Potentialmentioning
confidence: 99%
“…The ability to tan and propensity to sunburn when unprotected in the sunlight were classified in skin phototypes (Melsky et al, 1977). Skin phototype I subjects declared that they never tanned but (Mantel, 1963).…”
Section: Interviews and Questionnairementioning
confidence: 99%
“…protective glasses. In PUVA therapy, some acute minor effects have been reported, depending on the 8-MOP formulation and dose administered: nausea (3% to 51%) [16][17][18], headache (2%) [16], dizziness (1.5%) [16], pruritus (14% to 71%) [16,17]. A higher and earlier peak concentration has been observed when side effects were present (417 ng ml-' vs 280 ng ml-) [19].…”
Section: Pharmacokinetic Analysis Linearity Analysis Figures 1 and 2 mentioning
confidence: 99%
“…In primates receiving 2-18 mg kg-' 8-MOP orally, only dosedependent emesis, but no organ damage was observed [20]. Chronic surveillance of PUVA therapy has failed to identify any clinically relevant toxicity [16,21]. Also, a prospective study over 5 years examining ophthalmological findings in patients receiving PUVA indicated a small risk of ocular damage in patients who received at least 100 PUVA treatments [22].…”
Section: Pharmacokinetic Analysis Linearity Analysis Figures 1 and 2 mentioning
confidence: 99%